Identifikacija dejavnikov, ki vplivajo na izbiro izobraževalnega programa - Kogovšek, Tina (Teorija in praksa, 2007)
The article deals with the forming a coherent typology of factors that influence educational programme choice and vocational path. Argumentation is built on the principles of triangulation methodology, which enables observation of the same phenomenon with quantitative and qualitative approach.The basic starting points for identification of external factors, which influence the educational programme choice was first taken out from theoretical starting points. Further, the basic categories were analysed in detail on the basis of our own qualitative empirical study, which included management stuff of institutions of educational programmes, pupils and students. Coherence of gathered factors were further analysed with the help of "retrospective" survey on the employed individuals. On the basis of our findings we formed recommendations for theory and practice of career orientation.
Keywords: Occupational choice; Poklicna izbira; Kariera; Kariera people; Career; Education; Izobraževanje; izobraževalni programi; izbira poklica